My mum's going to explode - Strong, Jeremy; Clifford, Rowan, illus (London : Puffin, 2001)
Nicholas and his family are in a state of cofision when his mother becomes pregnant and her behavior becomes odd.
Keywords: Bahavior -- Fiction; Family life -- Fiction; Family-Juvenile fiction